Magnesium alloy conductive corrosion-resistant coating and preparation process thereof

CN122706185BActive Publication Date: 2026-10-30ZHUZHOU YIAN PRECISION MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611203989.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30
Estimated Expiration
2046-08-10

AI Technical Summary

Technical Problem

传统阳极氧化和微弧氧化可获得较厚的陶瓷层,耐磨性好,但膜层多孔且本身不导电,需配合封孔处理,难以满足导电要求

Benefits of technology

本发明所制备的镁合金表面涂层具有原位生长层状双氢氧化物底层、导电聚合物中间层和改性复合填料环氧表层的三层结构,其中层状双氢氧化物底层具有离子交换和屏蔽腐蚀介质的能力,中间层为聚苯胺或聚吡咯高分子聚合物,可以提供电子导电通路并兼具缓蚀作用;表层含有高导电复合填料,环氧涂层可以进一步降低接触电阻并阻隔外界侵蚀。通过三层的协同作用,使涂层在镁合金表面同时实现优异的导电性和长效耐腐蚀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to a magnesium alloy conductive corrosion-resistant coating and a preparation process thereof, and belongs to the technical field of magnesium alloy surface treatment. The coating comprises, from inside to outside, a layered double hydroxide bottom layer, an intermediate layer and a surface layer which are sequentially grown in situ; the intermediate layer is a polyaniline or polypyrrole layer prepared by an electrochemical method; and the surface layer is an epoxy resin coating containing composite fillers. The prepared coating has excellent conductivity and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnesium alloy surface treatment technology, and relates to a conductive and corrosion-resistant coating for magnesium alloy and its preparation process. Background Technology

[0002] Magnesium alloys have broad application prospects in defense and military industries due to their advantages such as low density, high specific strength and specific stiffness, and good machinability and casting properties. However, magnesium alloys are chemically reactive, and the spontaneously formed magnesium oxide film on their surface is loose and porous, making them highly susceptible to corrosion in humid environments or media containing chloride ions. This can lead to failure during service due to a decrease in their mechanical support.

[0003] Therefore, developing surface protective coatings that combine good electrical conductivity and corrosion resistance is one of the key technologies for expanding the application range of magnesium alloys. Traditional anodizing and micro-arc oxidation can obtain thick ceramic layers with good wear resistance, but the films are porous and non-conductive, requiring sealing treatment and making it difficult to meet conductivity requirements. Organic coatings have excellent shielding properties, but are usually electrical insulators. Adding conductive fillers can achieve conductivity, but high filler content often leads to decreased coating density and impaired corrosion resistance. Furthermore, the uniformity of filler dispersion in the resin matrix and the efficiency of conductive network construction still need to be improved. Summary of the Invention

[0004] The purpose of this invention is to provide a conductive and corrosion-resistant coating for magnesium alloys and its preparation process. The prepared coating has excellent conductivity and corrosion resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: A conductive and corrosion-resistant coating for magnesium alloy, the coating comprising, from the inside out: a layered double hydroxide underlayer, an intermediate layer and a surface layer; The intermediate layer is a polyaniline or polypyrrole layer prepared by an electrochemical method; The surface layer is an epoxy resin coating containing composite fillers, which are obtained by treating 1-butyl-3-methylimidazolium tetrafluoroborate and KH560 with sheet copper powder, carbon nanotubes and graphene oxide in a mass ratio of (5~8):(1~2):(0.5~1).

[0006] A process for preparing a conductive and corrosion-resistant coating for magnesium alloys includes the following steps: S1. Pretreatment of the magnesium alloy matrix; S2. The pretreated magnesium alloy substrate is placed in a solution containing magnesium salt, aluminum salt and urea, and a layered double hydroxide underlayer is grown on the surface of the magnesium alloy using a hydrothermal method. S3. An intermediate layer is deposited on the surface of the bottom layer by an electrochemical method. The electrolyte for the electrochemical method is a mixed solution of aniline or pyrrole monomer, p-toluenesulfonic acid, dispersant and water. S4. The surface coating is applied to the intermediate layer and cured to obtain the surface layer. The surface coating consists of the following components by weight: 40-60 parts of composite filler, 30-45 parts of epoxy resin, 4-6 parts of polyethylene glycol modified epoxy resin, 10-20 parts of solvent and 3-10 parts of curing agent.

[0007] In a preferred embodiment of the present invention, in step S2, the magnesium salt is magnesium nitrate; the aluminum salt is aluminum nitrate, wherein Mg... 2+ Concentrations range from 0.05 to 0.2 mol / L, Al 3+ The concentration is 0.025~0.1mol / L, and the urea concentration is 0.2~0.6mol / L.

[0008] As a preferred embodiment of the present invention, in step S2, the temperature of the hydrothermal reaction is 90~110℃ and the reaction time is 15~20h.

[0009] In a preferred embodiment of the present invention, in step S3, the electrochemical method is electrochemical cyclic voltammetry, with a scanning potential range of -0.2 to 1 V. SCE The scanning rate is 20~30mV / s, and the scanning cycle is 10~30 times.

[0010] As a preferred embodiment of the present invention, in step S3, the concentration of aniline or pyrrole monomer in the electrolyte is 0.1~0.3 mol / L, the concentration of dispersant is 0.1~0.3 mol / L, and the concentration of p-toluenesulfonic acid is 0.5~1 mol / L.

[0011] As a preferred embodiment of the present invention, in step S3, the dispersant is one of sodium dodecylbenzenesulfonate and polyvinylpyrrolidone.

[0012] As a preferred embodiment of the present invention, the preparation process of the composite filler in step S4 is as follows: Flake copper powder, carbon nanotubes and graphene oxide were mixed evenly to obtain a mixture, which was then added to ethanol and 1-butyl-3-methylimidazolium tetrafluoroborate. The mixture was stirred at 60-70℃ for 20-40 min, then KH560 was added and the mixture was stirred at 60-70℃ for 1-3 h. The mixture was then centrifuged and dried to obtain the composite filler.

[0013] As a preferred embodiment of the present invention, the ratio of 1-butyl-3-methylimidazolium tetrafluoroborate to the mixture is (1~3) mL: (50~70) g.

[0014] As a preferred embodiment of the present invention, the amount of KH560 added is 3 to 7% of the total mass of the mixture.

[0015] A uniform and dense layered double hydroxide (LDH) was formed in situ on the surface of a pretreated magnesium alloy matrix under hydrothermal conditions using a magnesium salt, aluminum salt, and urea system. The LDH exhibits a typical layered structure with exchangeable anions (NO3-) between the layers. - The toluenesulfonic acid provides an acidic environment, allowing aniline or pyrrole to become positively charged (aniline cation, pyrrole cation) under acidic conditions. These positively charged aniline or pyrrole cations can replace the inorganic anions between LDH layers through ion exchange and enter the interlayer. During electrochemical polymerization, the monomers between LDH layers are oxidized to cationic free radicals, leading to chain growth reactions and the formation of conductive polymer chains in the interlayer. Due to the limitations of the interlayer spacing, the polymer chains cannot grow indefinitely but alternate with the inorganic layers of LDH, forming a hybrid structure of alternating inorganic and organic layers. This allows for the partial intercalation of conductive polymers (polyaniline or polypyrrole) into the interlayer and interlamellar gaps of LDH while simultaneously forming polyaniline or polypyrrole. Furthermore, it allows for direct coverage of the LDH bottom layer, forming a continuous and dense conductive film, thereby improving conductivity. This structure not only enhances the bonding force between the intermediate polymer layer and the bottom LDH, preventing interfacial peeling, but also allows the polymer chains to fill the micropores and defects in the LDH layer, making the composite layer denser and significantly extending the penetration path of corrosive media.

[0016] In this invention, the surface filler is a mixture of sheet-like copper powder, carbon nanotubes, and graphene oxide. These three fillers are then synergistically modified with a 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid and a KH560 silane coupling agent. The ionic liquid can be adsorbed onto the filler surface via electrostatic / π-π interactions, effectively dispersing the filler. The silanol groups (Si-OH) generated after the hydrolysis of KH560 can react with the active hydroxyl groups on the filler surface (containing hydroxyl groups on the oxide layer of copper powder and the surface of graphene oxide), forming Si-OC or Si-OM (M being copper) covalent bonds, thus grafting onto the filler surface. After dual modification with ionic liquid and KH560, the dispersibility of the filler in epoxy resin and its interfacial bonding with the resin matrix are significantly improved, thereby forming a highly efficient conductive network and reducing resistance.

[0017] Adding polyethylene glycol-modified epoxy resin to the surface formulation can induce phase separation during the curing process, promoting the selective enrichment of conductive fillers in the PEG phase region, thereby improving the corrosion resistance of the coating without reducing its conductivity.

[0018] The beneficial effects of this invention are: The magnesium alloy surface coating prepared by this invention has a three-layer structure: an in-situ grown layered double hydroxide underlayer, a conductive polymer intermediate layer, and a modified composite filler epoxy surface layer. The layered double hydroxide underlayer possesses ion exchange and corrosive media shielding capabilities; the intermediate layer, composed of polyaniline or polypyrrole polymer, provides an electronic conductivity pathway and also acts as a corrosion inhibitor; the surface layer contains highly conductive composite filler, and the epoxy coating further reduces contact resistance and blocks external erosion. Through the synergistic effect of these three layers, the coating on the magnesium alloy surface simultaneously achieves excellent conductivity and long-term corrosion resistance. Detailed Implementation

[0019] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0020] It should be noted that, unless otherwise specified, the present invention does not specifically limit the source of the raw materials used in the following embodiments. Commercially available products or products prepared by conventional preparation methods that are well known to those skilled in the art can be used. Experimental methods that do not specify specific conditions are all conventional methods and conventional conditions well known in the art.

[0021] In the following examples and comparative examples: Flaky copper powder: Anhui Kerun Nanotechnology Co., Ltd., Product No.: KR-Cu-6, average particle size is 1. 10µm; Carbon nanotubes: Shanghai Maclean Biotechnology Co., Ltd., Product No.: G991390, Diameter: 20~40nm, Length: 1~2μm; Graphene oxide: Shanghai Maclean Biotechnology Co., Ltd., Model: G699086, Sheet diameter: 0.5~5μm, Thickness: 1~3nm.

[0022] The preparation process of polyethylene glycol modified epoxy resin is as follows: Epoxy resin and polyethylene glycol (PEG-400) were mixed in a molar ratio of 1:1, and 0.1 wt% of triphenylphosphine catalyst was added to the epoxy resin. The mixture was reacted at 80 °C for 6 h to prepare polyethylene glycol modified epoxy resin.

[0023] Example 1 S1. The AZ91D magnesium alloy substrate is subjected to pretreatment by grinding, degreasing and pickling activation. The magnesium alloy is ground with 400#, 800# and 1200# wet sandpaper in sequence, then ultrasonically cleaned in acetone for 10 minutes to remove oil, acid-washed and activated in 5wt.% oxalic acid solution for 30 seconds, ultrasonically cleaned with deionized water for 5 minutes, and finally air-dried at 25℃ to complete the pretreatment. S2. The pretreated magnesium alloy matrix is ​​placed in a solution containing magnesium nitrate, aluminum nitrate, and urea, and reacted at 100°C for 18 hours using a hydrothermal method to form a layered double hydroxide underlayer on the magnesium alloy surface; wherein Mg 2+ The concentration is 0.12 mol / L, Al 3+ The concentration is 0.05 mol / L, and the urea concentration is 0.4 mol / L; S3. An intermediate layer is deposited on the surface of the substrate using an electrochemical cyclic voltammetry method, with a scanning potential range of -0.2 to 1 V. SCE The scanning rate was 25 mV / s, the scanning cycle was 25 times, the concentration of pyrrole monomer in the electrolyte was 0.2 mol / L, the concentration of sodium dodecylbenzenesulfonate was 0.2 mol / L, and the concentration of p-toluenesulfonic acid was 0.8 mol / L. After completion, the electrolyte was washed with deionized water and then vacuum dried at 60℃ for 3 h. S4. By weight, mix 50 parts of composite filler, 38 parts of epoxy resin (E-51), 5 parts of polyethylene glycol modified epoxy resin, 15 parts of xylene and n-butanol in a volume ratio of 7:3, and 8 parts of curing agent polyamide 650. Disperse the mixture in a high-speed disperser at 1500 rpm for 30 min. Coat the mixture onto the intermediate layer and cure it at 80°C for 2 h to obtain the surface layer. The thickness of the surface layer is 50 μm. Preparation of composite fillers: Flake copper powder, carbon nanotubes, and graphene oxide were mixed evenly in a mass ratio of 6:1.5:0.8 to obtain a mixture. Then, ethanol was added, followed by 1-butyl-3-methylimidazolium tetrafluoroborate. The mixture was stirred at 65°C for 30 min, and then KH560 was added. The mixture was stirred at 65°C for another 2 h, and then centrifuged and dried to obtain a composite filler. The ratio of 1-butyl-3-methylimidazolium tetrafluoroborate to the mixture was 2 mL:60 g, and the amount of KH560 added was 5% of the total mass of the mixture.

[0024] Example 2 S1. The AZ91D magnesium alloy substrate is subjected to pretreatment by grinding, degreasing and pickling activation. The magnesium alloy is ground with 400#, 800# and 1200# wet sandpaper in sequence, then ultrasonically cleaned in acetone for 10 minutes to remove oil, acid-washed and activated in 5wt.% oxalic acid solution for 30 seconds, ultrasonically cleaned with deionized water for 5 minutes, and finally air-dried at 25℃ to complete the pretreatment. S2. The pretreated magnesium alloy matrix is ​​placed in a solution containing magnesium nitrate, aluminum nitrate, and urea, and reacted at 90°C for 15 hours using a hydrothermal method to form a layered double hydroxide underlayer on the magnesium alloy surface; wherein Mg 2+ The concentration is 0.05 mol / L, Al 3+ The concentration is 0.025 mol / L, and the urea concentration is 0.2 mol / L; S3. An intermediate layer is deposited on the surface of the substrate using an electrochemical cyclic voltammetry method, with a scanning potential range of -0.2 to 1 V. SCE The scanning rate was 20 mV / s, the scanning cycle was 10 times, the concentration of pyrrole monomer in the electrolyte was 0.1 mol / L, the concentration of sodium dodecylbenzenesulfonate was 0.1 mol / L, and the concentration of p-toluenesulfonic acid was 0.5 mol / L. After completion, the electrolyte was washed with deionized water and then vacuum dried at 60℃ for 3 h. S4. By weight, mix 40 parts of composite filler, 30 parts of epoxy resin (E-51), 4 parts of polyethylene glycol modified epoxy resin, 10 parts of xylene and n-butanol in a volume ratio of 7:3, and 3 parts of polyamide 650. Disperse the mixture in a high-speed disperser at 1500 rpm for 30 min. Coat the mixture onto the intermediate layer and cure it at 80°C for 2 h to obtain the surface layer. The thickness of the surface layer is 45 μm. Preparation of composite fillers: Flake copper powder, carbon nanotubes, and graphene oxide were mixed evenly in a mass ratio of 5:1:0.5 to obtain a mixture. Then, ethanol was added, followed by 1-butyl-3-methylimidazolium tetrafluoroborate. The mixture was stirred at 60°C for 20 min, and then KH560 was added. The mixture was stirred at 60°C for another 2 h. After centrifugation and drying, a composite filler was obtained. The ratio of 1-butyl-3-methylimidazolium tetrafluoroborate to the mixture was 1 mL: 50 g, and the amount of KH560 added was 3% of the total mass of the mixture.

[0025] Example 3 S1. The AZ91D magnesium alloy substrate is subjected to pretreatment by grinding, degreasing and pickling activation. The magnesium alloy is ground with 400#, 800# and 1200# wet sandpaper in sequence, then ultrasonically cleaned in acetone for 10 minutes to remove oil, acid-washed and activated in 5wt.% oxalic acid solution for 30 seconds, ultrasonically cleaned with deionized water for 5 minutes, and finally air-dried at 25℃ to complete the pretreatment. S2. The pretreated magnesium alloy matrix is ​​placed in a solution containing magnesium nitrate, aluminum nitrate, and urea, and reacted at 110°C for 20 hours using a hydrothermal method to form a layered double hydroxide underlayer on the magnesium alloy surface; wherein Mg 2+ The concentration is 0.2 mol / L, Al 3+ The concentration is 0.1 mol / L, and the urea concentration is 0.6 mol / L; S3. An intermediate layer is deposited on the surface of the substrate using an electrochemical cyclic voltammetry method, with a scanning potential range of -0.2 to 1 V. SCE The scanning rate was 30 mV / s, the scanning cycle was 30 times, the concentration of pyrrole monomer was 0.3 mol / L, the concentration of sodium dodecylbenzenesulfonate was 0.3 mol / L, and the concentration of p-toluenesulfonic acid was 1 mol / L. After completion, the sample was washed with deionized water and then dried under vacuum at 60℃ for 3 h. S4. By weight, mix 60 parts of composite filler, 45 parts of epoxy resin (E-51), 6 parts of polyethylene glycol modified epoxy resin, 10-20 parts of xylene and n-butanol in a volume ratio of 7:3 and 10 parts of polyamide 650, disperse in a high-speed disperser at 1500 rpm for 30 min, coat the intermediate layer and cure at 80℃ for 2 h to obtain the surface layer with a thickness of 60 μm. Preparation of composite fillers: Flake copper powder, carbon nanotubes, and graphene oxide were mixed evenly in a mass ratio of 8:2:1 to obtain a mixture. Then, ethanol was added, followed by 1-butyl-3-methylimidazolium tetrafluoroborate. The mixture was stirred at 70°C for 40 min, and then KH560 was added. The mixture was stirred at 70°C for another 3 h. After centrifugation and drying, a composite filler was obtained. The ratio of 1-butyl-3-methylimidazolium tetrafluoroborate to the mixture was 3 mL: 70 g, and the amount of KH560 added was 7% of the total mass of the mixture.

[0026] Example 4 It is basically the same as Example 1, except that the monomer in step S3 of this example is aniline.

[0027] Comparative Example 1 It is basically the same as Example 1, except that this comparative example did not go through step S2.

[0028] Comparative Example 2 It is basically the same as Example 1, except that this comparative example did not go through step S3.

[0029] Comparative Example 3 It is basically the same as Example 1, except that this comparative example did not go through step S4.

[0030] Comparative Example 4 This is basically the same as Example 1, except that in step S4 of this comparative example, the composite filler is simply a mixture of sheet copper powder, carbon nanotubes and graphene oxide in a mass ratio of 6:1.5:0.8.

[0031] Comparative Example 5 It is basically the same as Example 1, except that this comparative example only includes the LDH bottom layer.

[0032] Performance testing: 1. Corrosion resistance: Refer to GB / T 10125-2021, conduct a neutral salt spray test, test conditions: 5 wt.% NaCl solution, pH 6.5~7.2, temperature (35±2)℃, record the time when corrosion spots appear; 2. Adhesion: Cross-cut test, refer to ISO 2409; 2. Resistance: Measured using a resistance meter, the results are shown in Table 1 below: Table 1

[0033] Based on the above data, the salt spray time of Examples 1-4 is ≥1350h, indicating that the three-layer full structure of the present invention (LDH + conductive polymer intermediate layer + epoxy surface layer) can provide excellent long-term corrosion protection for magnesium alloy surfaces. The corrosion resistance time of Comparative Example 1 is reduced to 1196h, about 16% lower than Example 1, indicating that the LDH bottom layer plays an important role in delaying the penetration of corrosive media from the matrix interface, and the intermediate layer directly contacts the magnesium alloy, thus providing a more direct conductive path. The resistance is slightly higher than Example 1, but the overall resistance is still low. The corrosion resistance time of Comparative Example 2 is 1123h, about 21% lower than Example 1. This indicates that the conductive polymer intermediate layer not only provides conductivity but also enhances corrosion resistance through densification and active corrosion inhibition. Since there is no conductive polymer intermediate layer, and conductivity relies solely on the surface modified filler, the resistance increases significantly, indicating that the intermediate layer is crucial for constructing efficient conductive pathways. Comparative Example 3 exhibited a corrosion resistance time of 1274 hours, approximately 10% lower than Example 1. This indicates that the surface epoxy coating provides both physical shielding and can be further densified by the modified filler within it. Therefore, the absence of the surface layer leads to decreased corrosion resistance and a higher resistance than Example 1, suggesting that the surface epoxy coating helps to further reduce contact resistance. In Comparative Example 4, the filler was not modified with ionic liquid and KH560, resulting in poor filler dispersion and weak interfacial bonding in the surface coating, leading to increased micropores and reduced corrosion resistance. Simultaneously, the unmodified filler resulted in poor dispersion, leading to a discontinuous conductive network and a significant increase in resistance. Comparative Example 5 showed the worst corrosion resistance time at only 990 hours, indicating that while a single LDH layer provides some protection, it is far less effective than a three-layer composite structure.

[0034] The adhesion of Examples 1-4 and Comparative Example 4 was all grade 0. These samples all contained a complete three-layer structure or a surface layer, indicating that a good interfacial bond was formed between the surface layer, the intermediate layer, and the substrate.

[0035] The resistance, corrosion resistance and adhesion of the above embodiments are all better than those of the comparative examples. Furthermore, according to the comparative example data, the absence of a certain structural layer or the lack of modification of the filler will lead to a decrease in conductivity or corrosion resistance.

[0036] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A conductive and corrosion-resistant coating for magnesium alloys, characterized in that, The coating comprises, from the inside out, a layered double hydroxide underlayer, an intermediate layer, and a surface layer; The intermediate layer is a polyaniline or polypyrrole layer prepared by an electrochemical method, and the electrolyte of the electrochemical method is a mixed solution of aniline or pyrrole monomer, p-toluenesulfonic acid, dispersant and water. The surface layer is an epoxy resin coating containing composite fillers, which are obtained by treating 1-butyl-3-methylimidazolium tetrafluoroborate and KH560 with sheet copper powder, carbon nanotubes and graphene oxide in a mass ratio of (5~8):(1~2):(0.5~1).

2. A preparation process for a magnesium alloy conductive and corrosion-resistant coating as described in claim 1, characterized in that, Includes the following steps: S1. Pretreatment of the magnesium alloy matrix; S2. The pretreated magnesium alloy substrate is placed in a solution containing magnesium salt, aluminum salt and urea, and a layered double hydroxide underlayer is grown on the surface of the magnesium alloy using a hydrothermal method. S3. An intermediate layer is deposited on the surface of the bottom layer using an electrochemical method; S4. The surface coating is applied to the intermediate layer and cured to obtain the surface layer. The surface coating consists of the following components by weight: 40-60 parts of composite filler, 30-45 parts of epoxy resin, 4-6 parts of polyethylene glycol modified epoxy resin, 10-20 parts of solvent and 3-10 parts of curing agent.

3. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S2, the magnesium salt is magnesium nitrate; The aluminum salt is aluminum nitrate, wherein Mg 2+ Concentrations range from 0.05 to 0.2 mol / L, Al 3+ The concentration is 0.025~0.1mol / L, and the urea concentration is 0.2~0.6mol / L.

4. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S2, the temperature of the hydrothermal reaction is 90~110℃, and the reaction time is 15~20h.

5. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S3, the electrochemical method is electrochemical cyclic voltammetry, with a scanning potential range of -0.2 to 1 V. SCE The scanning rate is 20~30mV / s, and the scanning cycle is 10~30 times.

6. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S3, the concentration of aniline or pyrrole monomer in the electrolyte is 0.1~0.3 mol / L, the concentration of dispersant is 0.1~0.3 mol / L, and the concentration of p-toluenesulfonic acid is 0.5~1 mol / L.

7. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S3, the dispersant is one of sodium dodecylbenzenesulfonate and polyvinylpyrrolidone.

8. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 2, characterized in that, In step S4, the preparation process of the composite filler is as follows: Flake copper powder, carbon nanotubes and graphene oxide were mixed evenly to obtain a mixture, which was then added to ethanol and 1-butyl-3-methylimidazolium tetrafluoroborate. The mixture was stirred at 60-70℃ for 20-40 min, then KH560 was added and the mixture was stirred at 60-70℃ for 1-3 h. The mixture was then centrifuged and dried to obtain the composite filler.

9. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 8, characterized in that, The ratio of 1-butyl-3-methylimidazolium tetrafluoroborate to the mixture is (1~3) mL: (50~70) g.

10. The preparation process of the magnesium alloy conductive and corrosion-resistant coating according to claim 8, characterized in that, The amount of KH560 added is 3-7% of the total mass of the mixture.

Citation Information

Patent Citations

  • Magnesium alloy surface oxide modified conductive corrosion-resistant coating and preparation method thereof

    CN118791892A

  • ZK61M magnesium alloy surface corrosion-resistant coating as well as preparation method and application thereof

    CN120082884A